Ranking the Leading Risk Factors for Sudden Unexpected Death in Epilepsy - DeGiorgio, Christopher M.; Markovic, Daniela; Mazumder, Rajarshi; Moseley, Brian D. (Frontiers in Neurology, 2017)
Background Sudden unexpected death in epilepsy (SUDEP) is rare in well-controlled epilepsy. However, SUDEP is a common cause of death in drug-resistant epilepsy. Over the last 30 years, multiple cohort and population studies have identified clinical risk factors associated with an increased risk for SUDEP. Objective To identify and rank the leading SUDEP risk factors from major cohort and population-based studies. The incidence of SUDEP is also evaluated in special clinical situations, including antiepileptic drug treatment, epilepsy surgery, devices, and assignment to placebo in clinical trials. Methods A PubMed search for English language human cohort studies for the terms Sudden, Death, and Epilepsy was performed for the years 1987–2017. Risk factors for SUDEP were identified and ranked by the weighted log adjusted odds ratio (OR)/relative risk ratio (RR). Findings The top 10 leading risk factors ranked from highest to lowest log adjusted OR/RR are the following: ≥3 GTC seizures per year; ≥13 seizures in the last year; No Antiepileptic Drug (AED) treatment; ≥3 AEDs; ≥3 GTCs in the past year; 11–20 GTC seizures in the last 3 months; age of onset 0–15 years old; IQ < 70; 3–5 AED changes in the last year; ≥3 AEDs. Two risk factors from separate sources (≥3 GTC seizures and ≥3 AEDs) occur twice in the top 10 risk factors. Conclusion The top 10 risk factors for SUDEP are identified and ranked. A ranking of the top risk factors could help clinicians identify patients at highest risk for SUDEP.